Terapi Pijat Punggung Effleurage terhadap Intensitas Nyeri Akut Pasca Bedah Fraktur Tulang Panjang - Lubis, Yuni Suharnida; Tanjung, Dudut; Ardinata, Dedi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study examines the effect of effleurage back massage therapy on the intensity of acute pain after long bone fracture surgery. This research method is true experimental with a pretest-posttest control group design. The results showed a significant difference between the NSAID and NSAID groups with effleurage with a p-value <0.05. The range of changes in VAS in the NSAID group with effleurage tended to be higher than in the NSAID group on days 3 and 4. The conclusion is that NSAIDs with effleurage are effective in reducing the intensity of acute pain in patients after long bone fracture surgery and are recommended as a nursing intervention. Independently to ease the pain intensity of fracture patients. Keywords: Effleurage, Fracture, Pain